Aflatoxin status of some commercial dry dog foods in Ibadan, Nigeria (2012)
The occurrence of aflatoxins B1, B2, G1 and G2 in commercial dry dog foods in the city of Ibadan, Southwest Nigeria, was investigated. Dry dog food samples from 6 producers were purchased on five different occasions from retail outlets in Ibadan, Nigeria. High performance liquid chromatography was used for separation and quantification of aflatoxin fractions, after consideration of the limits of detection and quantification of the method. Results indicate that aflatoxins B1, B2, G1 and G2 were detected in all the samples investigated, with B1 being the most abundant. The range of concentration of total aflatoxins was 7.76 to 11.93 μg/kg (mean: 9.61 μg/kg). The results show that dry dog foods marketed in Ibadan are frequently contaminated with aflatoxins, exposing dogs to adverse effects of aflatoxicosis. Scientifically based regulations for the acceptable limit of mycotoxins in pet foods in the country would be beneficial.